Comparative analysis of N95 respirators fit testing with commercially available and in house reagent. Issue 3 (September 2021) - Khan, Erum; Farooqi, Joveria; Shafaq, Humaira; Khushik, Kaleem Ullah; Raza, Syed Shamim; Khan, Sara; Rafiq, Zohra; Ahmed, Bushra; Chisti, Shazia; Imtiaz, Kehkashan; Zafar, Hasnain; Zafar, Afia
Summary: Background: Due to COVID-19, thousands of healthcare workers have been affected and have lost their lives in the line of duty. For the protection of healthcare workers, WHO and CDC have made standard guidelines and requirements for PPE use. N95 masks are amongst the most readily used PPE by healthcare professionals and it is highly recommended by OSHA that every make and model of N95 should go through a fit test at least once in a year. Method: A total of 30 randomly selected healthcare professionals (who were a regular user of N95 respiratory masks) were subjected to assess in-house (saccharin sodium benzoate) reagent for use for standard qualitative fit testing in our hospital. Threshold testing with the in-house reagent at three different concentrations was performed prior to establish participants' sensitivity to the reagent. After successful completion of threshold testing, fit test was performed on participants wearing an N95 mask. Results: All the participants included in the study passed the sensitivity testing with three concentrations of the reagents, while it was concluded that the concentration of the in-house reagent that was well suited for the sensitivity testing was a concentration of 1g/dl saccharin with 10g/dl sodium benzoate. For fit testing 12g/dl was found to be more appropriate. Discussion: Our study provided a low cost solution to ensure safety of healthcare workers who are regular users of N95 masks following guidelines implemented by OSHA and CDC. Conclusion: The in-house test solution prepared was found to be equally sensitive to its commercially available counterpart.